Developing seedless growth of atomically thin semiconductor layers: Application to transition metal dichalcogenides. Issue 13 (September 2018) - Rahmani Taji Boyuk, Mohammad Reza; Sovizi, Saeed; Ghanbari, Hajar; Simchi, Abdolreza; Aboudzadeh, Neda
Abstract: Controlled growth of atomic monolayers of IV-VII transition metal dichalcogenides (TMDs) has provided unprecedented opportunities to fabricate modern optoelectronic nanodevices. However, synthesis of large-area and high quality two-dimensional TMDs is still challenging. We have synthesized WS2 and MoS2 nanosheets by atmospheric pressure chemical vapor deposition (APCVD) at wide-range of processing conditions. The nanostructures were analyzed by optical and confocal microscopy, atomic force microscopy, Raman spectroscopy, and X-ray diffraction to determine the thickness, lateral size and structure of the deposits. Through designing and performing of a set of controlled experiments as well as comparing the attained results with others, we present a general roadmap for APCVD of atomically thin WS2 and MoS2 nanosheets. The appropriate working windows for the controlled synthesis are established. For the controlled growth of 2D WS2 crystals, relatively low growth temperature (750 °C) can be utilized. It is shown that an oxide mass to the gas flow rate of 0.004 favorably results in the formation of 2D WS2 . Monolayers and few layers might be processed at higher temperatures (≥ 800 °C) at an oxide mass/gas flow rate ratio of 2–3. The seedless growth of MoS2 nanosheets is more complicated than WS2 possessing with narrower working window. A minimum temperature of 575 °C is required to provide enough oxide vapor pressure for deposition; otherwise, no deposits are formed. Above 650 °C, achieving 2D nanolayers is tricky due to massive deposition of the metal oxide from the vapor phase forming thick layers. In the intermediate range, however, there is a possibility to attain 2D nanostructures through fine controlling of the oxide mas/gas flow rate. Finally, it is shown that through precise control of the processing parameters, a controllable growth of the nanosheets without pre-seeding at lower temperatures and shorter times is feasible.